Deferasirox (ICL670A) effectively inhibits oesophageal cancer growth in vitro and in vivo. (25th February 2013) - Ford, SJ; Obeidy, P; Lovejoy, DB; Bedford, M; Nichols, L; Chadwick, C; Tucker, O; Lui, GYL; Kalinowski, DS; Jansson, PJ; Iqbal, TH; Alderson, D; et al.
Abstract : Background and Purpose: Growing evidence implicates iron in the aetiology of gastrointestinal cancer. Furthermore, studies demonstrate that iron chelators possess potent anti‐tumour activity, although whether iron chelators show activity against oesophageal cancer is not known. Experimental Approach: The effect of the iron chelators, deferoxamine (DFO) and deferasirox, on cellular iron metabolism, viability and proliferation was assessed in two oesophageal adenocarcinoma cell lines, OE33 and OE19, and the squamous oesophageal cell line, OE21. A murine xenograft model was employed to assess the effect of deferasirox on oesophageal tumour burden. The ability of chelators to overcome chemoresistance and to enhance the efficacy of standard chemotherapeutic agents (cisplatin, fluorouracil and epirubicin) was also assessed. Key Results: Deferasirox and DFO effectively inhibited cellular iron acquisition and promoted intracellular iron mobilization. The resulting reduction in cellular iron levels was reflected by increased transferrin receptor 1 expression and reduced cellular viability and proliferation. Treating oesophageal tumour cell lines with an iron chelator in addition to a standard chemotherapeutic agent resulted in a reduction in cellular viability and proliferation compared with the chemotherapeutic agent alone. Both DFO and deferasirox were able to overcome cisplatin resistance. Furthermore, in human xenograft models, deferasirox was able to significantly suppress tumour growth, which was associated with decreased tumour iron levels. Conclusions and Implications: The clinically established iron chelators, DFO and deferasirox, effectively deplete iron from oesophageal tumour cells, resulting in growth suppression. These data provide a platform for assessing the utility of these chelators in the treatment of oesophageal cancer patients. Linked Article: This article is commented on by Keeler and Brookes, pp. 1313–1315 of this issue. To view this commentary visit http://dx.doi.org/10.1111/bph.12093